Imaging optically induced neural activity in the brain - Mahadevan-Jansen, Anita (2010)
Infrared neural stimulation (INS) is well characterized for the peripheral nervous system; however, translation to the central nervous system (CNS) presents a new set of challenges which require us to consider different anatomy, multiple cell types, and the physiology associated with structures in the CNS. This study presents our first attempt to translate INS to in vivo stimulation of the CNS and to image the related response. The results from this study show that INS generates intrinsic optical signals of similar magnitude and shape associated with well characterized mechanical stimuli. The implications of this work could lead to neural implants which allows for single cell stimulation making it possible to design closed loop neural prosthetics.